Synthesis, Characterization and Quantum Mechanical Study of Some New 2-benzylidenehydrazinecarbothioamide Derivatives as Corrosion Inhibitors for Carbon/mild Steel in Acidic Medium - R. Al-Jeilawi, Oday H.; A. H. Al-Yassiri, Muntadar (Iraqi Journal of Science, 2023)
In this work, some of new 2-benzylidenehydrazinecarbothioamide derivativeshave been prepared by condensation of thiosemicarbazide and different substitutedaromatic benzaldehydes in presence of glacial acetic acid to give compounds (1-6),these compounds have characterized by its physical properties and spectroscopicmethods. This work also included theoretical study to prove the ability of thesecompounds as corrosion inhibitors; The program package of Gaussian 09W with itsgraphical user interface GaussView 5.0 had used for this purpose; the methods ofDensity Functional Theory (DFT) with basis set of 6-311G (d,p) / hybrid function ofB3LYP and semiempirical method of PM3 have been used, the study includedtheoretical simulation to simulate the reactivity of these compounds as corrosioninhibitors for carbon steel in gas phase, aqueous medium and in acidic medium(acidic medium is a medium contains acid that able to protonate these compoundsand change them to protonated form), some parameters have calculated in bothprevious methods such EHOMO, ELUMO, ΔEL-H, Ionization Potential (I), ElectronAffinity (A), electronegativity (χ), Global Hardness (η), Atomic Charges, DipoleMoment (μ) and Fraction of Electron Transferred from Inhibitor Molecules to theMetallic Atoms (ΔN), the resulted parameters showed that these compounds arebehaving as inhibitors for corrosion of carbon steel.